Long-term, in vivo therapeutic effects of a single dose of miR-145 micelles for atherosclerosis - Deborah D. Chin; Neil Patel; Woori Lee; Sonali Kanaya; Jackson Cook; Eun Ji Chung (Bioactive Materials, 2023)
Atherosclerosis is a chronic inflammatory disease that is characterized by the build-up of lipid-rich plaques in the arterial walls. The standard treatment for patients with atherosclerosis is statin therapy aimed to lower serum lipid levels. Despite its widespread use, many patients taking statins continue to experience acute events. Thus, to develop improved and alternative therapies, we previously reported on microRNA-145 (miR-145 micelles) and its ability to inhibit atherosclerosis by targeting vascular smooth muscle cells (VSMCs). Importantly, one dose of miR-145 micelles significantly abrogated disease progression when evaluated two weeks post-administration. Thus, in this study, to evaluate how long the sustained effects of miR-145 micelles can be maintained and towards identifying a dosing regimen that is practical for patients with chronic disease, the therapeutic effects of a single dose of miR-145 micelles were evaluated for up to two months in vivo. After one and two months post-treatment, miR-145 micelles were found to reduce plaque size and overall lesion area compared to all other controls including statins without causing adverse effects. Furthermore, a single dose of miR-145 micelle treatment inhibited VSMC transdifferentiation into pathogenic macrophage-like and osteogenic cells in plaques. Together, our data shows the long-term efficacy and sustained effects of miR-145 micelles that is amenable using a dosing frequency relevant to chronic disease patients.